PSYCHIATRIC DISORDER COMORBIDITY IN CHRONIC NEUROMUSCULOSKELETAL PAIN IN ATMA JAYA HOSPITAL - Yaputra, Faldi; Barus, Jimmy (Jurnal Kedokteran YARSI, 2017)
Background : This study describe comorbid psychiatric disorder especially in depressive disorder, anxiety disorder and sleep disturbance in chronic neuromusculoskeletal pain patients.Objective : The aim of this research is to measure the prevalence of psychiatric comorbidity in choric neuromusculoskeletal pain.Methods : Cross sectional study with consecutive sampling method is used in this study. The data are collected in the neurology clinic in Atma Jaya Hospital, Jakarta between July ? December 2015. Diagnostic and Statistical Manual of Mental Disorder (DSM) V criteria was used to diagnose the psychiatric condition. Results : The data were obtain from 55 study samples, consist of 12 males (21,8%), 43 females (78,2%). Thirty of them are ? 60 years old (55%) and 25 are ? 60 years old (45%). The most common is low back pain 30 patients (55%). Non-neuropathic pain 12 patients (22%), and neurophatic pain 43 patients (78%). The most common pain intensity is severe, Visual Analog Scale (VAS) ?8 (43%). The most common psychiatric disorder is insomnia (20%), followed by anxiety and insomnia (16,3%), and anxiety (12,7%).Discussion : Majority of chronic pain has psychiatric disoder comorbidity, coexisting condition should be considered in evaluation, diagnosis, and therapy.Conclusions : Chronic pain usually accompanied by psychiatric disorder, so thorough evaluation, diagnosis and therapy have to be fully addressed to achieve optimum functionality and good quality of life.Suggestions : Next study should collect samples from some hospitals and design the analitic study that can explain association between factors that can influence the comorbidity.